La préhistoire de l’enseignement de l’occitan à travers quelques manuels et traités pédagogiques - Marie-Jeanne Verny (Lengas)
There is still a lot of data to be collected and analyzed concerning the relationship between the school and the "patois", beyond the well-known phenomena of linguistic repression. A certain number of works from the end of the 19th to the beginning of the 20th century, manuals or pedagogical treatises, by granting a certain pedagogical function to the "patois" reveal an attitude that is more complex than what is generally believed. This attitude does not escape the diglossic prejudices on the functional inequality of languages. It is this complexity that we are trying to approach here through a comparative study of the words and productions of Michel Bréal, Canon Aurouze and Brother Savinien.